Positive Psychology Intervention (PPI) Program for Persons Who Use Drugs (PWUDS): A Pilot Study - Argel B. Masanda (SAGE Publishing, 2024)
Building on the premises of Positive Psychology, this undertaking conducted a pilot study of the designed 14-session Positive Psychology Intervention (PPI) program established based on the character strengths and virtues (CSV) of persons who use drugs (PWUDs) to assess its usefulness, delivery details, and impacts. Conducted in one of the biggest Drug Abuse Treatment and Rehabilitation Center in the Philippines, 24 PWUDs were randomly selected by the program staff to participate in its pilot run while securing all necessary ethical guidelines and requirements. Via within-subjects pretest-posttest experimental design, the especially adapted and developed tools were used to assess the PWUDs' progress as they were facilitated by the said program. Results yielded significant improvements in the PWUDs' mental wellbeing ( M   =   1.29 , SD =  0.35; t (21) = 9.30, P  < .00001), life satisfaction ( M   =   1.82 , SD  =   0.24; t (21) = 9.89, P  < .00001), and psychological functioning ( M   =   1.65 , SD  =   0.19; t (21) = 8.58, P  < .00001). Moreover, the PWUDs regarded the designed PPI program very highly and experienced it with positive outcomes, especially for their CSVs. Further improvement of the said program centers around proper time allotment, number of participants in the program sessions, appropriate activities per session, including specific ice breaker games, activity materials needed, and the proper sequencing of each session. These data are used to improve the PPI program structures and components. Pertinent conclusions about the gathered data were drawn, and relevant recommendations were also thereby provided.